Fecal microbiota changes associated with dehorning and castration stress primarily affects light-weight dairy calves - Mir, Raies A. (PLoS One, 2019)
Gastrointestinal tract (GIT) microbiota and stress can impact animal health. Studies have shown that perturbations in the GIT microbiota can influence host health and productivity by affecting physiological homeostasis, metabolism, hematopoiesis and inflammation. The present study aimed to evaluate possible effects of dehorning and castration stress on the GIT microbiota of dairy calves. Dehorning and castration are routinely performed on over 90% of dairy farms, and analgesics like flunixin meglumine (FLU) are given at the time of these procedures to reduce pain. We analyzed fecal microbiota of 24 weaned male dairy calves at two different stages in their life (at 10 weeks for dehorning and 36 weeks age for castration) to determine any GIT microbiota changes due to these stressful procedures and the FLU treatment. Dehorning was performed using an electrocautery dehorner applied to the horn for 10 seconds, and surgical castration was used as the castration method. Our analysis showed that the Shannon diversity index was significantly higher in animals that were not dehorned compared to dehorned animals. Castration stress also resulted in a significant decrease in Shannon diversity index, which was more pronounced in lower weight calves. Body weight and stress had significant effects on the taxonomic profiles of the GIT microbiota. There was a significant difference in the GIT bacterial community structure between heavy- and light-weight calves at Day 3 after castration but not at Day 0 (prior to castration). Our results indicate that dehorning and castration stress reduced microbial diversity of the GIT microbiota, but only in light-weight calves. This work is important for elucidating biological effects of stress on dairy calves and identifying potential modulation points in the microbiota of these food-producing animals to improve animal health and production.